The diagnostic accuracy of point-of-care nucleic acid-based isothermal amplification assays for scrub typhus: a systematic review and meta-analysis - Dixit, Rashi; Manikandan, Sandeep; Prakash, John Antony Jude; Biswal, Manisha; Mohapatra, Dharitri; Gopalan, Natarajan; Gnanamani, G.; Behera, Sujit Kumar (Frontiers in Microbiology, 2025)
IntroductionThe diagnosis and detection of pathogens such as Rickettsia and Orientia is a cause of major concern among the public health community. Unavailability of rapid, cost-effective diagnostic assays contributes to delayed diagnosis and timely treatment. Using the methodology of systematic reviewing and meta-analysis, the study aimed to synthesize and compare the diagnostic performances of all the available isothermal assays for the detection of classical rickettsial diseases.MethodsStudies were retrieved from PubMed and Scopus, and selection and screening were conducted using pre-determined inclusion and exclusion criteria. Analysis was performed using Meta-DiSc 2.0 for the assessment and comparison of diagnostic performance of the isothermal assays.ResultsOverall, six studies were selected as a part of this systematic review. All the selected studies (n = 6) optimized LAMP as their index test to detect scrub typhus. The quality assessment of the selected studies revealed only (n = 1) study to be of poor quality with a QUADAS-2 score of (<2). Meta-analysis revealed the pooled sensitivity of LAMP to be 66% [95% CI (0.40–0.85)] with a pooled specificity of 94% [95% CI (0.81–0.98)]. LAMP was estimated with a positive likelihood ratio of 8.3 [95% CI (3.8–18.1)] and a negative likelihood ratio of 0.3 [95% CI (0.2–0.7)] with a false positivity rate of 0.07 [95% CI (0.02–0.2)]. The diagnostic odds ratio was reported to be 21.96 [95% CI (10.2–47.3)]. Due to severe heterogeneity in the body of evidence (I2 = 0.77), a meta-regression was performed with certain covariates to explore the potential causes. A case–control design was found to exaggerate the sensitivity {0.84 [95% CI (0.5–0.9)]} and specificity {0.73 [95% CI (0.6–0.8)]}.ConclusionThe findings reveal subpar performance of LAMP for the detection of scrub typhus. Active research and development focused on optimization of novel molecular diagnosis that are efficient, rapid, and cost-effective shall foster timely diagnosis and aid in reduction of the overall burden of scrub typhus.Protocol and registrationA detailed protocol of this review is registered and available in Prospero at: https://www.crd.york.ac.uk/prospero/. (registration number CRD42024511706).